An updated checklist of Neotropical Plecoptera - Pessacq, Pablo (2019)
Since the publication of the Catalogue of Neotropical Plecoptera of Froehlich in 2010, the description of 85 new species and further taxonomical changes raises the number of valid names to 596, most of them belonging to the highly speciose Anacroneuria.